Megalobrama amblycephala IL-22 attenuates Aeromonas hydrophila induced inflammation, apoptosis and tissue injury by regulating the ROS/NLRP3 inflammasome axis - Wang, Zhensheng; Zhai, Wenya; Liu, Hong (Frontiers in Immunology, 2024)
Mammalian interleukin-22 (IL-22) attenuates organismal injury by inhibiting reactive oxygen species (ROS) and impeding the NLRP3 inflammasome activation. However, the role of fish IL-22 in this process remains unclear. We characterized MaIL-22, an IL-22 homolog in blunt snout bream (Megalobrama amblycephala). Despite its low sequence identity, it shares conserved structures and close evolutionary relationships with other teleost IL-22s. Furthermore, Aeromonas hydrophila (A. hydrophila) infection leads to tissue injury in M. amblycephala immune organs and concomitantly altered Mail-22 mRNA expression, suggesting that MaIL-22 was involved in the antimicrobial immune response. To explore MaIL-22's biological functions, we produced recombinant MaIL-22 (rMaIL-22) protein and demonstrated it significantly enhanced the survival of M. amblycephala post-A. hydrophila infection. To unravel its protective mechanisms, we explored the ROS/NLRP3 inflammasome axis and its downstream signaling responses. The results showed that rMaIL-22 treatment significantly elevated antioxidant enzyme (T-SOD, CAT and GSH-PX) activities to inhibit MDA activity and scavenge ROS in visceral tissues. Meanwhile, rMaIL-22 impeded the activation of NLRP3 inflammasome by suppressing NLRP3 protein and mRNA expression. This indicated that rMaIL-22 contributed to inhibit A. hydrophila-induced activation of the ROS/NLRP3 inflammasome axis. Consistent with these findings, rMaIL-22 treatment attenuated the expression of proinflammatory cytokines (il-1β, tnf-α and il-6) and proapoptotic genes (caspase-3 and caspase-8) while promoting antiapoptotic genes (bcl-2b and mcl-1a) expression, ultimately mitigating tissue injury in visceral tissues. In conclusion, our research underscores MaIL-22's key role in microbial immune regulation, offering insights for developing IL-22-targeted therapies and breeding programs.